2006
DOI: 10.1177/000348940611500308
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Administration of Rofecoxib versus Ketoprofen for Pain Relief after Tonsillectomy

Abstract: Oral premedication with rofecoxib seems to be more effective than use of ketoprofen in decreasing postoperative pain and the need for opioid rescue medication after elective tonsillectomy. Both drugs seem to be relatively safe as far as postoperative bleeding is concerned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…We can use paracetamol, tramadol, NSAID, or weak or strong opioids for rescue analgesia after tonsillectomy or adenotonsillectomy [9][10][11]. We chose tramadol for rescue analgesia during the first 6 postoperative hours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We can use paracetamol, tramadol, NSAID, or weak or strong opioids for rescue analgesia after tonsillectomy or adenotonsillectomy [9][10][11]. We chose tramadol for rescue analgesia during the first 6 postoperative hours.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies emphasized that morphine doses were reduced and less opioid was required for the postoperative pain management when ketamine was added to morphine [10,16,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Before being pulled from the market, preoperative Vioxx had been favorably compared to intramuscular ketoprofen [55] . In contrast, another study showed no significant difference between preoperative Vioxx, acetaminophen and placebo [56] . Investigations into preoperative analgesics will likely continue as we learn more about pain physiology.…”
Section: Discussionmentioning
confidence: 86%
“…A previous study reported that oral ketoprofen, a nonselective NSAID, was too short-acting for overnight pain relief after tonsillectomy [20]. A single oral premedication with rofecoxib, a COX-2 inhibitor, was more effective than two intramuscular ketoprofen doses (before surgery and after 12 hrs) in decreasing postoperative pain and opioid rescue analgesic consumption after tonsillectomy [21]. A single preoperative dose of IV flurbiprofen, another nonselective NSAID, relieved immediate postoperative pain after tonsillectomy, but its effects were limited to a few hours [22].…”
Section: Discussionmentioning
confidence: 98%
“…In postoperative pain management, lornoxicam has a potency similar to morphine [5], tramadol [16], and meperidine [19]. Several NSAIDs have been administered perioperatively in previous studies [20][21][22]. A previous study reported that oral ketoprofen, a nonselective NSAID, was too short-acting for overnight pain relief after tonsillectomy [20].…”
Section: Discussionmentioning
confidence: 99%